Effect of Interferon-γ on the Basal and the TNFα-Stimulated Secretion of CXCL8 in Thyroid Cancer Cell Lines Bearing Either the RET/PTC Rearrangement Or the BRAF V600e Mutation - Mario Rotondi; Francesca Coperchini; Oriana Awwad; Patrizia Pignatti; Christian A. Di Buduo; Vittorio Abbonante; Flavia Magri; Alessandra Balduini; Luca Chiovato (Mediators of Inflammation)
CXCL8 displays several tumor-promoting effects. Targeting and/or lowering CXCL8 concentrations within the tumor microenvironment would produce a therapeutic benefit. Aim of this study was to test the effect of IFNγ on the basal and TNFα-stimulated secretion of CXCL8 in TCP-1 and BCPAP thyroid cancer cell lines (harboring RET/PTC rearrangement and BRAF V600e mutation, resp.). Cells were incubated with IFNγ (1, 10, 100, and 1000 U/mL) alone or in combination with TNF-α (10 ng/mL) for 24 hours. CXCL8 and CXCL10 concentrations were measured in the cell supernatants. IFNγ inhibited in a dose-dependent and significant manner both the basal (ANOVA F: 22.759; p<0.00001) and the TNFα-stimulated (ANOVA F: 15.309; p<0.00001) CXCL8 secretions in BCPAP but not in TPC-1 cells (NS). On the other hand, IFNγ and IFNγ + TNF-α induced a significant secretion of CXCL10 in both BCPAP (p<0.05) and TPC-1 (p<0.05) cells. Transwell migration assay showed that (i) CXCL8 increased cell migration in both TPC-1 and BCPAP cells; (ii) IFNγ significantly reduced the migration only of BCPAP cells; and (iii) CXCL8 reverted the effect of IFNγ. These results constitute the first demonstration that IFNγ inhibits CXCL8 secretion and in turn the migration of a BRAF V600e mutated thyroid cell line.